Situation Report: Poland, 11 June 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Sejm and the Party Meets / by Marian Barczewski People's Councils Elections Campaign / by Janusz Bugajski Father of Murdered Solidarity Activist Alleges Police Cover-Up / by Janusz Bugajski; Ryszard Kolaczkowski Awkward Questions for Polish Government Spokesman / by Janusz Bugajski Poland's Dying Forests / by Ewa Celt Sundry Items